Mathematical simulation of separation flows with large zones of recirculation - Шквар, Є. О. (Proceedings of National Aviation University (archive), 1998)
Proposed is mathematical model and numerical method of calculation of turbulent separation flows which are characterized by formation of reversible flow of large dimensions behind the separation zone. Given is an example of calculation of flow characteristics which develop over vacuum combination created in streamlined surface and steps